The Dignity of Indonesian Language in Information Technology - Safinatul Hasanah Harahap; Frinawaty Lestarina Barus; Atika Wasilah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The attitude of language is illustrated in the use of language in public spaces. The use of Indonesian language is required in submission of information to the public. Submission of information using the Indonesian language in information technology is a dignity forms of Indonesian language. This study is aimed to describe the use of Indonesian language in information technology. The research method used is descriptive method with a qualitative approach. The source of research data is the website of cluster one tertiary institutions in Indonesia. The data used are menu and submenu which is on the main website in the college website. The results showed that there are still menu and submenu that use foreign languages/terms. Therefore, the dignity of Indonesian language in information technology has not yet been reached maximally. The solution to these problems is the making of policies related to the use of Indonesian language in targeted information technology.